The Convergence of Sovereign Environmental, Social and Governance Ratings - Bouye, Eric (World Bank, Washington, DC, 2021)
This paper studies sovereign environmental, social, and governance (ESG) ratings from the qualitative and quantitative angles. First, it introduces the landscape for sovereign ESG ratings. Second, it provides a comparison with the history of credit ratings, factoring in that ESG ratings are in an early development stage. Third, the paper reviews different actors, key issues, including taxonomy, models and data from different providers. The paper provides a qualitative assessment of the convergence of ratings among providers by introducing a factor attribution method, that maps all providers' ratings into a common taxonomy defined by the United Nations-supported Principles for Responsible Investment (UNPRI). Then, a quantitative analysis of the convergence is performed by regressing the scores on variables from the World Bank sovereign ESG database. A noticeable contribution to the literature is a high level of explanatory power of these variables across all rating methodologies, with a R2 ranging between 0.78 and 0.98. An analysis of the importance of variables using a lasso regression exhibits the preponderance of the governance factor and the limited role of demographic shifts for all providers.